Multiplicidade dos padrões de sustentabilidade na indústria global de óleo de palma - Hidalgo, Laura Mercedes Grimaldo (Universidade Federal de São Carlos, 2021)
The growing impact on the environment of the global production of agricultural commodities has created new regulations that aim at a more sustainable production. Thus, sustainability standards (SS) are seen as a tool for transnational trade governance because they increase the possibility that commercialized products come from sustainable sources. However, there is currently a proliferation of SS in almost every industry. This dissertation examined the palm oil market, an important and rapidly growing industry worldwide. Hence, it proposed to explore the ways in which SS multiplicity affects trade costs. The study took into account the major SS in global palm oil production such as Roundtable on Sustainable Palm Oil - RSPO; International Standard for Carbon Certification - ISCC; Roundtable on Sustainable Biomaterials – RSB; Indonesian Sustainable Palm Oil – ISPO and Malaysian Sustainable Palm Oil - MSPO. An analytical model was developed that seeks to establish the potential effects of the SS multiplicity on trade costs. By considering the interactions between patterns such as competition, cooperation, and overlap, the model assesses the possible direct and indirect effects on trade costs for producers. The results point out high overlap and balanced co-opetition (a phenomenon that combines competition and cooperation) in the standard market. Private standards had a low potential to create trade costs on its members, especially the RSPO. However, ISPO had the greatest potential to cause trade costs due to its low levels of cooperation and overlap. Furthermore, the results showed that the dynamics of co-opetition would be generating learning and innovation processes in the standard market without ceasing the competition for new members. Finally, this type of interaction still drives an increase in certification, implementation and packaging costs for producers.
Multiplicity of sustainability standards in the global palm oil industry
Keywords: Palm oil; Sustainability standards; Sustainability multiplicity; Trade costs; Óleo de palma; Padrões de sustentabilidade; Multiplicidade de padrões; Custos de comércio; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INTERNACIONAL::RELACOES DO COMERCIO; POLITICA COMERCIAL; INTEGRACAO ECONOMICA